KONSUMSI DAN PRODUKSI MUSIK DIGITAL PADA ERA INDUSTRI KREATIF - Cahya Berto Habibi; Irwansyah Irwansyah (Metacommunication: Journal of Communication Studies, 2020)
The development of technology makes new practices in consuming music in the digital age. Music fans and connoisseurs are facilitated in accessing music every day, this is not spared from the large role of digitalization, so that music lovers can access their music anywhere. Consumption of digital music has made music producers look for new ways of producing music, which used to be done analogously to digital, where the direction of sales changed from what is usually done by retail stores changed to digital markets. With changing production and consumption patterns, several companies have provided a medium for publication and consuming music to appreciate these musicians and avoid piracy. Medium (Platform) that is used in the same way as digital music stores, by subscribing to listen to all the music in the company's database. The ease of production and consumption of music can be accessed on several platforms such as Spotify, Joox, and Apple Music. The method used in this paper is a desk review by collecting secondary data from various scientific sources, such as: journal articles, websites, and a collection of reports on music in the digital age.